STANDAR FISIK IDEAL DALAM PERSPEKTIF BUDAYA DAN KESEHATAN (Kasus: Obesitas Pada Etnis Bugis) - Mas'ud, Hikmawati (Media Kesehatan Politeknik Kesehatan Makassar, 2017)
Ideal Physical Standard be dream each people, but that is be problematic both the culture and the health perspective. The conception need a study by comprehensive in order to overcome a dichotomy given availabel. This research aim to confirm any view of the culture and health perspective about Ideal Physical Standard. A qualitative descriptive by Grand Theory used an approach of this research. Any data collected by observation, interviews and documentation. A qualitative used to analyze data. The result of this research indicated that An Ideal Physical Standard view of the culture perspective are body compact and full content, better face and confirmity to look in it, face like baby face, give a happy in feeling to touch her/him, and bigger and good in growth. For the health perspective, Ideal Physical Standard oriented to Body Mass Indeks (BMI) < 27.0, male abdominal circumference <90 cm and women <80 cm. There are different at using a parameter both them. The health using a quantitative to determining a Ideal Physical Standard, but the Culture using a qualitative, so be gap them.Therefore, they need synergy and integrated them in order to general standard which expected can be received them.